IMPACT OF ETHICAL LEADERSHIP TYPES ON SERVICE SABOTAGE BEHAVIOR, MEDIATOR ROLE OF ETHICAL CLIMATE; A CASE STUDY OF PAKISTAN EDUCATION INSTITUTE - Kashif Javed; Dr. Khalil Ur Rehman; Dr. Abdul Rasheed (International Journal of Contemporary Issues in Social Sciences, 2023)
The main aim of study is to assess the effect of ethical leadership three types i.e., (1) Leader Human Orientation, (2) Leader Responsibility Orientation, and (3) Leader Justice Orientation on Service Sabotage Behaviour, Mediator role of ethical climate. Study motivated with Pakistan education institute employee’s ethical standard. Study used 313 participant education institute employees’ data and applied descriptive, correlation, regression and robustness test for estimation. Result of study indicated Leader Human Orientation and Leader Responsibility Orientation are 1% highly significant impact on service sabotage behaviour. Meanwhile Leader Justice Orientation is 10% significant impact on service sabotage behaviour, therefore, mediator Inverse influencing impact on ethical leadership types, when mediator applied Leader Justice Orientation influence role increase and Leader Human Orientation and Leader Responsibility Orientation influence role reduced. Robustness indicated all variable are highly important for education sector due to employee’s behaviour, and for quality of work. Ethical principles not established in education institute a solid route cause for employee’s service sabotage behaviours. Educational Employee’s behaviour highly important for institution, quality of work maintains through employees efficient behaviour and ethical leadership role enhance when education institute implement ethics and avoid behaviour reactions, therefore ethical leader must focus on employee’s behaviour to avoid service sabotage behaviour.